Structural changes and the differential expression of osteoprotegerin (OPG) and receptor activator of nuclear factor kB ligand (RANKL) in subchondral bone during the development of osteoarthritis - AKMAN, AKMA AZMIERA; Talib, Ain Aisyah; Md Yusof, Azirah; Khalid, Kamarul Ariffin; Yusof, Nurul Asyiqin; Abdul Ghani, Radiah; Hamdan, Asmah Hanim; Zamli, Zaitunnatakhin (2018)
Osteoarthritis is a degenerative joint disease that is characterized by subchondral bone changes. These changes may be associated with bone remodelling, which involve coordinative functions between bone formation and resorption markers such as osteoprotegerin (OPG) and receptor activator of nuclear factor kB ligand (RANKL), respectively. Previous studies have shown that the structural changes were different between the subchondral bone plate and trabecular bone. However, the expression of bone formation and bone resorption markers underlying the differences between these two regions has yet to be determined. Hence, the present study aims to determine the structural changes and expressions of OPG/RANKL in the subchondral bone plate and trabecular bone during the development of osteoarthritis in Dunkin Hartley guinea pigs. Eighteen tibias were scanned using a micro-computed tomography at three different time points; 10, 20 and 30 weeks of age to determine their subchondral bone plate and trabecular bone thickness. Immunohistochemistry and histopathology methods were conducted to determine the expression of OPG/RANKL and microscopic osteoarthritis score, respectively. The results showed that subchondral bone plate and trabecular bone thickness were greater in the medial than the lateral side of the tibial plateau, and increased significantly with ageing (p < 0.01). In addition, across the time points, the OPG/RANKL ratio of medial Sbp initially increased, before decreasing at the final time point. In contrast, the OPG/RANKL ratio of medial Tb was initially constant but then decreased at 30 weeks of age. Interestingly, a significant correlation was observed between the subchondral bone plate thickness and OPG/RANKL ratio with microscopic osteoarthritis scores (r = 0.5, p < 0.05), suggesting that the subchondral bone plate plays an important role in the pathogenesis of osteoarthritis.